Librarian working with Islamic collections: Malaysian experience - Wan Mamat, Wan Ali (Faculty of Information Management, Universiti Teknologi Mara, 2013)
Literature revealed that studies on the history of books or bibliography show the glaring focus on western books rather than Eastern and Islamic book production. The development of libraries in Muslim world, such as the mosque library, royal library, public library and private library has be neglected. The problem arises mainly because of the weakness of Muslim themselves. Prior to the midle age, the Muslims were in the frontline in the development of knowledge, but since then, the development of knowledge, albeit knowledge on Islamic religion were monopolized mainly by Europeans. During the period there were hundreds of universities in Muslim world. Almost every major cities, such as Cairo, Baghdad, Cordoba, Damascus etc. have universities. The same condition happened with library development in Muslim societies. The development of libraries and universal knowledge declined substantially since then, except on Islamic religion. The library development and services which were not given proper attention.